2012
DOI: 10.4236/health.2012.411165
|View full text |Cite
|
Sign up to set email alerts
|

The study of technology acceptance for e-wallets application of clinic fees payment

Abstract: The purpose of this study was to investigate the demand of application of e-wallet in domestic retail industry by examining the needs of adoption of small amount paying method and the reasons for customers’ using of IC stored value card in this industry and aimed at providing suggestions on the e-development of small amount paying methods for domestic retail and banking industries. This study was developed in a way that the model constructs in TAM were adapted to the context of using e-wallets for clinic fees.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 8 publications
0
8
1
Order By: Relevance
“…Their acceptance of e-money is more influenced by the enjoyment of using e-money, the information about e-money, and personal information credibility. In this case, the results of this study do not support previous studies that show that PU and PEOU positively influence users' intention to use (16), (17), (18), (19). However, the previous study supported the results of this study regarding the effect of PE (1), (20), and PC (3) on behavioral intention.…”
Section: Results and Findingscontrasting
confidence: 99%
“…Their acceptance of e-money is more influenced by the enjoyment of using e-money, the information about e-money, and personal information credibility. In this case, the results of this study do not support previous studies that show that PU and PEOU positively influence users' intention to use (16), (17), (18), (19). However, the previous study supported the results of this study regarding the effect of PE (1), (20), and PC (3) on behavioral intention.…”
Section: Results and Findingscontrasting
confidence: 99%
“…PEOU influences attitude, which in turn influences the intention to use m-coupons (Jayasingh and Eze, 2010). Lai (2012) showed that the PU, the PEOU is positively associated with users' attitude toward using, and the PEOU is positively associated with the PU. Arvidsson (2013) found that the most important factor explaining whether consumers are likely to use a mobile payment service is PEOU.…”
Section: Perceived Ease Of Usementioning
confidence: 99%
“…With the birth of e-commerce, one of the mobile payment methods: e-wallet has emerged to provide consumer transactions with convenience and confidence not only in virtual marketplace but also in entity shops. Lai (2012) have analysed the factors that enable consumers to use e-wallets for clinic fees in Taipei, and added prior information technology experience to the TAM; they found that the more positive a person's experience about an object is, the more positive beliefs he or she will hold about it. People had preference only for the useful and easily operation of payment (Lai, 2012).…”
Section: Mobile Payment In Physical Storesmentioning
confidence: 99%
See 1 more Smart Citation
“…One type of mobile payment is an e-wallet. According replied ( 2008), e-wallet can replace the use of cash, with the proviso that, the e-wallet should facilitate transactions without carrying cash is thick and heavy and e-wallet should reduce the user performs the calculation of transactions in order to speed up payments and e-wallet must improve security and reduce the risk of loss from theft and ensure the anonymity of the payment [13][14][15].…”
Section: Introductionmentioning
confidence: 99%